PENERAPAN PEMBELAJARAN GROUP INVESTIGATION (GI) DENGAN POLA LESSON STUDY TERHADAP KEMAMPUAN MEMECAHKAN MASALAH SISWA KELAS X MA SABILURRASYAD NW BARABALI TAHUN PELAJARAN 2018/2019 - Muh. Zaini Hasanul Muttaqin (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
Education has a central role in increasing development and it is one aspect to improve human resources. The problem that is still found in the world of education is the low ability of students to solve a problem, especially in biology subjects so that it requires an action that can overcome these problems, one of which is by changing the learning process for the better. The purpose of this study was to determine the effect of the Application of Group Investigation (GI) Learning with Lesson Study Patterns on the Problem Solving Ability of Class X MA Sabilurrasyad NW Barabali Students in the academic year 2018/2019. This type of research is experimental research using Quasi Experimental Design. The populations in this study were students of class X semester II which consisted of 2 classes with a total of 37 students. The sample in this study was class X IPA as an experimental class and class X IPS as a control class using simple random sampling technique. The instrument in this study was a test in the form of an essay test, which consisted of 8 questions. Based on the results of data analysis, the average post-test score for the experimental class was 74.2 and the control class was 66.17. While the hypotheses test using statistical analysis with the t-test formula at the 5% confidence level is obtained t-count of 3.418. After being compared with t-table 1.690, then tcount 3,418> t-table 1,690, so the conclusion in this study is that there is an effect of the Implementation of Group Investigation (GI) Learning with Lesson Study Patterns with Lesson Study Patterns on the Ability to Solve Problems in Class X MA Sabilurrasyad NW Barabali in the academic year 2018/2019.